UNUSUAL FOREIGN BODIES IN GIT - Muhammad, Gul; Rahman, Syed Jamil-ur-; Bangush, Assad (Journal of Ayub Medical College Abbottabad, 1993)
A wide variety of foreign bodies have been found in the gastrointestinal tract and ingenious methods have been used for their removal. Recently several reports have shown the usefulness of fibropticendoscopes in removing foreign bodies from upper and lower parts of GIT. In this report we describe a child in whom nature and number of foreign bodies necessitated the use of rigid sigmoidoscopes for removal.